PENGARUH BRAND CREDIBILITY TERHADAP WORD OF MOUTH MELALUI CUSTOMER SATISFACTION DAN CUSTOMER LOYALTY PADA GIANT HYPERMARKET DI SURABAYA - ANDREAS, JULIUS (Universitas Katolik Widya Mandala Surabaya, 2012)
The development of retail business which are growing rapidly encourage company to compete in maintaining existing customers and acquire new customers by implanting a good store brand credibility (store name) in the minds of customers so that customers be satisfied, loyal, and created a positive word of mouth.Â The purpose of this study was to determine the effect of Brand Credibility on Word Of Mouth through Customer Satisfaction and Customer Loyalty as an intervening variable in Giant Hypermarket Surabaya. The sampling technique used in this study is a non probability sampling. Meanwhile, the analysis technique is using Structural Equation Modeling (SEM) with Linear Structural Relation program (Lisrel). Respondents were taken from 150 customers of Giant Hypermarket in Surabaya with particular characteristics. The results showed that Customer Satisfaction and Customer Loyalty is an intervening variable between Brand Credibility on Word Of Mouth, there is influence of Brand Credibility on Customer Satisfaction and Customer Loyalty, there is influence of Customer Satisfaction and Customer Loyalty on Word Of Mouth, and there is influence of Customer Satisfaction on Customer Loyalty.